К познанию личинок поденок рода Paraleptophlebia (Epheme roptera, Paraleptophlebiidae) - Байкова, О.Я. (Вестник зоологии, 1976)
Rare larvae of May-Flies from the Paraleptophlebia Lest genus are described. An identification key of species occurring in the territory of the USSR in the Far East water bodies is given. The title P. cothurnata T s h e r n., 1952 is reduced to the synonym of P. chocolata I m a n., 1937.